2007
DOI: 10.1002/ijc.22581
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Vx‐2 rabbit tumors with ανβ3‐integrin‐targeted 111In nanoparticles

Abstract: Earlier tumor detection can improve 5-year survival of patients, particularly among those presenting with cancers less than 1 cm in diameter. a m b 3 - Targeted 111 In nanoparticles (NP) were developed and studied for detection of tumor angiogenesis. Studies were conducted in New Zealand white rabbits implanted 12 days earlier with Vx-2 tumor. a m b 3 - Targeted 111 In/NP bearing 10 111In/NP vs. 1 111In/NP nuclide payloads were compared to nontargeted radiolabeled control particles. In vivo competitive bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
99
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 18 publications
12
99
0
Order By: Relevance
“…Although liposomal delivery of cytotoxic drugs can improve antitumor activity, targeted delivery of these particles represents a potential approach to further enhance efficacy and minimize toxicity. Recent studies have described the design of NPs that target the tumor endothelium to improve diagnosis via imaging (5,6,17) or deliver therapeutics to solid tumors (8,18,19). The majority of the therapeutic research has focused on using various forms of RGD peptides for targeting integrin ␣v␤3, which is present on the tumor neovasculature (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although liposomal delivery of cytotoxic drugs can improve antitumor activity, targeted delivery of these particles represents a potential approach to further enhance efficacy and minimize toxicity. Recent studies have described the design of NPs that target the tumor endothelium to improve diagnosis via imaging (5,6,17) or deliver therapeutics to solid tumors (8,18,19). The majority of the therapeutic research has focused on using various forms of RGD peptides for targeting integrin ␣v␤3, which is present on the tumor neovasculature (20).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently described technical details of a perfluorocarbon nanoemul-sion vesicle that appears capable of serving as a selectively targeted carrier that remains stable after insertion of melittin, which might serve to deliver the melittin in vivo (19). Our nanovehicle carriers are synthesized as an oil-in-water emulsion composed of a liquid perfluorooctyl bromide (PFOB) core having a monolayer of phospholipid forming a stabilizing interface with the aqueous media (20)(21)(22)(23)(24). We have illustrated the stable incorporation of melittin into the outer lipid monolayer of these nanovehicles by surface plasmon resonance, fluorescence, and circular dichroism spectroscopy (19).…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al designed an indium-111 labeled perfluorocarbon nanoparticle targeted to v 3 , an integrin characteristically overexpressed in tumor neovasculature. In a rabbit model, the authors demonstrated a high sensitivity, low-resolution signal for tumor vasculature (Hu et al 2007). Perfluorocarbons NP may also be used for MRI (Schmieder et al 2005) allowing for a dual modality probe in the future that would increase this resolution while maintaining sensitivity.…”
Section: Single Modality Carriersmentioning
confidence: 99%